2010
DOI: 10.1590/s0102-311x2010000900017
|View full text |Cite
|
Sign up to set email alerts
|

Desigualdades regionais na prevalência de diagnóstico de asma em crianças: uma análise da Pesquisa Nacional por Amostra de Domicílios, 2003

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
4
0
6
Order By: Relevance
“…Em indivíduos na faixa etária infantil (entre 0 e 9 anos de idade) que participaram da PNAD 2003 que utilizou o diagnóstico médi-co como critério para o diagnostico de asma ou bronquite, houve uma prevalência média nacional de 8,1%. Já na faixa etária acima dos 18 anos, esta prevalência foi de 12% 29 .…”
Section: Resultsunclassified
“…Em indivíduos na faixa etária infantil (entre 0 e 9 anos de idade) que participaram da PNAD 2003 que utilizou o diagnóstico médi-co como critério para o diagnostico de asma ou bronquite, houve uma prevalência média nacional de 8,1%. Já na faixa etária acima dos 18 anos, esta prevalência foi de 12% 29 .…”
Section: Resultsunclassified
“…A study carried out in the South of Brazil in 2003, with secondary data referring to the Brazilian population extracted from PNAD and its health supplement, showed that being a child of parents with black skin color, living in agglomeration and in low standard households were associated with the diagnosis of asthma. 23 The report of health problems in the 15 days preceding the interview resulted in a PR that was two times higher for asthma, when compared to the individuals who did not report health problems. Asthmatic individuals frequently present daily diffi culties due to the health problems related to the disease, especially associated allergies, infections of the upper airways, emotional alterations and sleep disorders.…”
Section: Discussionmentioning
confidence: 98%
“…Black skin color associated with higher prevalence of asthma has been observed in other studies, corroborating our result. 1,11,23 Children with non-white skin color belonging to the cohort of individuals born in 1993 in the city of Pelotas presented at the age of six and seven a relative risk 1.9 (95%CI 1.1;3.3) times higher for asthma in comparison to those with white skin color. 6 The fi ndings seem to be consistent with the hypothesis that biological differences play an important role in the occurrence of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the highest prevalences of asthma in males, when compared to females, can be explained by physiological disadvantages. 23 Boys at this age tend to have higher IgE concentrations than girls, 19 in addition to lower respiratory fl ow rates. 10,17 Asthma management conditions in Brazil are below what is ideal.…”
Section: Discussionmentioning
confidence: 98%